PERLINDUNGAN HUKUM TERHADAP ORANG YANG MEMINJAMKAN DATA PRIBADINYA UNTUK KEPERLUAN PEMBELIAN OBJEK ATAU BARANG TERTENTU - Friska Sonya Yolanda; Sartika Dewi; Muhamad Abas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was carried out because it is still common for debtors to transfer fiduciary property to third parties without the agreement of creditors, resulting in losses and legal ambiguity for creditors. Fiduciary collateral is really governed by Law No. 42 of 1999, which gives creditors privileged status and legal protection. Examining the legal protection provided to creditors with regard to the transfer of fiduciary collateral and the possible legal remedies in the case of such a violation is the goal of this study. By examining laws, legal literature, and other pertinent legal resources, the research methodology uses normative legal research using a normative juridical perspective. The results show that both preventative and repressive techniques are used to give creditors legal protection. The formation of genuine deeds, the requirement to register fiduciary security, and the ban on moving the subject of security without the creditor's approval are preventive measures that provide protection. Repressively, creditors have access to civil legal remedies, such as claims for tort, violation of contract, and enforcement of fiduciary security, as well as criminal penalties. When a fiduciary collateral item is transferred without authorisation, creditors have a number of legal options at their disposal. These remedies include enforcing the fiduciary collateral object and civil remedies include bringing a tort and breach of contract case. Additionally, creditors may pursue criminal remedies by reporting the debtor to the authorities if the debtor is found to have committed a legal violation. These measures are taken to protect the creditor’s rights and provide legal certainty regarding the agreement that has been entered into.